A NEW SPECIES OF TAPINURUS FROM THE CAATINGA OF PIAUI, NORTHEASTERN BRAZIL (SQUAMATA, TROPIDURIDAE) - Manzani, P. R.; Abe, Augusto Shinya [UNESP] (Herpetologists League, 1990)
Tapinurus helenae sp. nov. is described from northeastern Brazil. The species is characterized by a dorsoventrally depressed body three bluish-white longitudinal stripes, the middorsal one interrupted at the scapular area, and an ochre colored dorsum that is lacking in larger males. Tapinurus helenae is easily distinguished from the other two known species, T. semitaeniatus and T. pinima, by its interrupted middorsal stripe. The new species inhabits calcareous massifs and sandstones in forested caatinga at the Toca de Cima dos Pilao, Sao Raimundo Nonato, Piaui, northeastern Brazil.
Keywords: REPTILIA; SQUAMATA; TROPIDURIDAE; TAPINURUS-HELENAE SP-NOV